2017
DOI: 10.1097/mib.0000000000001076
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Pertussis Booster Vaccination in Children and Adolescents with Inflammatory Bowel Disease

Abstract: Booster dose of pertussis vaccine was immunogenic and safe in pediatric patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Some studies investigated multiple vaccines ( Table 1 ). The studies covered the non-live vaccines against Diphtheria Tetanus Polio (DTP, 6 studies), Hepatitis A virus (HAV, 4 studies), Hepatitis B virus (HBV, 7 studies), Human Papillomavirus (HPV, 4 studies), Influenza (13 studies), Meningococcus C (1 study) and Pneumococci (both the pneumococcal conjugate vaccination (PCV) and/or the 23-valent pneumococcal polysaccharide vaccine (PPSV-23) vaccine, 6 studies) ( 9 50 ). In addition, studies were included that reported on the live-attenuated vaccines against Measles, Mumps and Rubella (MMR, 12 studies, including 3 on the combined MMR-Varicella booster) ( 12 14 , 51 59 ), Varicella Zoster Virus (VZV, 5 studies) ( 59 63 ), one study which included 1 patient with oral polio vaccine ( 59 ) and one case report on the Bacillus Calmette-Guérin (BCG) vaccine ( 64 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies investigated multiple vaccines ( Table 1 ). The studies covered the non-live vaccines against Diphtheria Tetanus Polio (DTP, 6 studies), Hepatitis A virus (HAV, 4 studies), Hepatitis B virus (HBV, 7 studies), Human Papillomavirus (HPV, 4 studies), Influenza (13 studies), Meningococcus C (1 study) and Pneumococci (both the pneumococcal conjugate vaccination (PCV) and/or the 23-valent pneumococcal polysaccharide vaccine (PPSV-23) vaccine, 6 studies) ( 9 50 ). In addition, studies were included that reported on the live-attenuated vaccines against Measles, Mumps and Rubella (MMR, 12 studies, including 3 on the combined MMR-Varicella booster) ( 12 14 , 51 59 ), Varicella Zoster Virus (VZV, 5 studies) ( 59 63 ), one study which included 1 patient with oral polio vaccine ( 59 ) and one case report on the Bacillus Calmette-Guérin (BCG) vaccine ( 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the 2011 recommendations, six cohort studies including in total 650 pedAIIRD patients and 2219 healthy controls assessed the DTP (3 diphtheria, 1 pertussis, 4 tetanus) vaccination, with a maximum level of evidence of 2B for immunogenicity and safety (adverse events) ( 9 14 ). Efficacy was not evaluated; all studies assessed immunogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…An increased prevalence of rheumatoid arthritis has been reported in UC patients. Previous studies have also demonstrated that the pertussis vaccine was immunogenic and safe in pediatric patients with UC, particularly when used in combination with anti-TNF- α agents [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most observational studies have shown no significant differences in immunogenic response between pediatric or adult patients with IBD irrespective of immunosuppressive therapy, or healthy controls ( 15 , 53 , 148–151 ). One study suggested that adults with IBD may have lower diphtheria and pertussis antibody concentrations compared to healthy subjects, with those on anti-TNF therapy having lower concentrations compared to those on thiopurine monotherapy ( 151 ).…”
Section: Inactivated Vaccines In Patients With Inflammatory Bowel Diseasementioning
confidence: 99%